Digitalisasi Zakat dalam Upaya Meningkatkan Kesejahteraan Sosial dan Pemulihan Ekonomi Nasional selama Pandemi Covid-19 - Listiana, Arum Nanda; Khairunnisa, Berliana; Nasution, Naura Nabila; Afna, Shofi Balqissafira (Diponegoro Journal of Islamic Economics and Business, 2022)
This study analyzes the effectiveness of the role of digitizing zakat in social welfare and national economic recovery during the Covid-19 pandemic. This study aims to understand the role of the distribution of zakat digitalization to provide welfare and encourage economic recovery during the Covid-19 pandemic in Indonesia. In the current era of the Covid-19 pandemic, this study provides insight for policy makers  to be able to manage the consequences of the pandemic innovatively. To facilitate muzakki to make it easier to pay zakat, BAZNAS of the Republic of Indonesia has innovation  by issuing a digital zakat platform. The collection of zakat funds at BAZNAS of the Republic of Indonesia has increased even in the midst of the Covid-19 pandemic. The method used in this research is descriptive qualitative analysis which is an effort to find out the events in the object of research, then carried out with a library research approach. Meanwhile, to analyze the data using content analysis technique, which is a method used to find out a conclusion from a text. Based on observations, it was found that the absorption of funds carried out by zakat management institutions had increased quite well in overcoming economic problems during the Covid-19 pandemic.